Perspektif Remaja GPP Aek Nauli Tentang Praktik Mengasihi (Teladan Bunda Teresa) - Sihombing, Warseto Freddy; Manullang, Megawati; Lumban Gaol, Ester Novita (NABISUK : Jurnal Teologi dan Pelayanan, 2024)
This research is motivated by the problem of adolescents who experience many problems about love that no longer appear to surface both in the midst of society and especially fellow Christian adolescents because human life is hit by a crisis of faith characterized by high egoism, arrogance, envy, spite, an attitude that does not care about others who are lacking, loss of brotherhood, loss of mutual respect,  depletion of fraternal ties, The breakup of the help-relief union, forcing one's own will on others and disrespect for each other in GPP teenager Aek Nauli.  This study aims to find out how the practice of loving others, especially for GPP teenager Aek Nauli by emulating Mother Teresa in terms of love. This study used descriptive qualitative method. The author collects data from various literature sources in the form of theological journals, articles or books that are in accordance with the topic that is the subject of study. Researchers make observations on the phenomenon of today's adolescent life. Where Mother Teresa's practice of loving is to love sincerely, She loves everyone, because She sees the face of Jesus in whom She loves. Youth as future successors of the church must know the life of love through the teachings of the Bible, so as to increasingly live the practice of love taught by God by imitating Mother Teresa.